Decision Making and Learning in a Globalizing World - Otto H. Swank; Bauke Visser (Tinbergen Institute, 2010)
We study two aspects of globalization. It allows a decision-maker to go beyond his own local experience and to learn from other decision-makers in addressing common problems. This improves the identification and diffusion of best practices. It also provides extra information to `markets' that evaluate decision-makers: comparisons become possible. We identify conditions under which the globalization of markets helps or hurts (i) the communication among decision-makers about their own experience and (ii) the quality of the decision that is taken next. An important mediating factor is whether decision-making is centralized or decentralized.
Keywords: D83; D70; D02; 330; centralization; decentralization; learning; cheap talk; reputational concerns; globalization; policy diffusion; Globalisierung; Politische Entscheidung; Dezentralisierung; Entscheidungstheorie